La2NiO4 nanoparticles as a core host of sulfur to enhance cathode volumetric capacity for lithium–sulfur battery. (20th August 2022) - Ge, Hai-Lun; Wang, Zhen-Yu; Li, Guo-Ran; Liu, Sheng; Gao, Xue-Ping
Abstract: Lithium–sulfur battery is recognized as one of the most promising next-generation energy storage devices. But the volumetric energy density of sulfur cathode is insufficient as compared with the cathodes of the commercial lithium-ion batteries owing to the low tap density of nonpolar and light-weight carbon materials as sulfur hosts. In this work, for the first time, La2 NiO4 (LNO) nanoparticles uniformly coated around carbon nanotubes (CNTs) are introduced as the host of sulfur cathode for lithium–sulfur battery. The polarity of LNO delivers the high electrocatalytic activity towards intermediate soluble lithium polysulfides by a strong chemical interaction. Benefiting from the synergistic effect of LNO nanoparticles and CNTs, the CNT@LNO host accelerates the conversion kinetics of sulfur species. Consequently, the S-CNT@LNO composite exhibits improved cycling stability with a slow capacity decay rate (0.088% per cycle) at 1 C for 500 cycles. Importantly, the high tap density of 1.49 g cm −3 for this composite promises a high volumetric capacity of 1486.07 mAh cm −3 at 0.05 C, almost 2.6 times higher than that of the S-CNT composite. This work provides a practicable strategy to improve the cycling stability and high-volumetric capacity of sulfur cathodes.